An Experiment in Computer Supported Collaborative Learning (CSCL) on an Undergraduate Business Module - Mackie, Sarah; Beeby, Mick (Proceedings of the International Conference on Networked Learning, 2002)
The paper reports on the conduct and the theoretical foundations of an on-going educational research project conducted within an undergraduate business degree programme at the Bristol Business School, UWE. It also contains some preliminary findings. The project seeks to facilitate student group work through the introduction of computer supported collaborative learning (CSCL) and to evaluate its consequences for effective learning as measured by the task achievement and member satisfaction in three different types of student teams. The study also seeks to ascertain the extent to which team effectiveness is moderated (if at all) by students conceptions of learning and approaches to study.